Planejamento tributário : estudo de caso em uma empresa de serviços em montagem de estrutura metálica - Antunes, Valdeci (2023)
Tax planning is an important management tool at the service of companies. This case study in a company in the field of services in the assembly of metallic structures, aims to identify the least costly tax regime for the company, between the real profit and presumed profit regimes. The study also explored the assessment of taxation options for the INSS and the possibility of opting for the levy on the company's gross revenue. The work began with a bibliographical research on the subject. The methodology of the work was to carry out a case study with a descriptive approach with quantitative analysis in order to identify the amount due for IRPJ, CSLL, PIS and COFINS taxes, for each tax regime and the amounts due from the employer's INSS based on calculation between the CPRB and payroll. The results indicate that with the adherence to the taxable income regime, the annual tax burden projected for the year 2024, in the quarterly modality, will be R$ 3,042,162.51; while in the annual modality BRL 3,026,300.83; and in Presumed Profit R$ 4,165,455.03; indicating a difference between the quarterly actual profit, annual actual profit and presumed profit regime. The analysis of the regimes in optimistic and pessimistic scenarios also made it possible to reinforce the decision, for the year 2024, for the annual real profit, since in the evaluated scenarios and the values ​​showed that the annual real profit is the regime that generates the lowest tax burden.